English as an international language in Viet Nam: history and development. Issue 2 (4th May 2018) - Doan, Ngoc; Pham, Toan; Pham, Min; Tran, Kham
Abstract: This article reviews the spread of English to Viet Nam since 1950s, analyzing important policies which have influenced the role of English in Viet Nam. The review indicates that English is used for both international and intra-national communication, a prominent feature being the growing use of English as a medium of instruction (EMI). We argue that it is not appropriate to frame the status of English in Viet Nam using the English-as-a-foreign-language (EFL)–English-as-a-second-language (ESL) binary, but that English is moving towards English as a lingua franca (ELF) and English as an international language (EIL). However, current ELF and EIL conceptualizations do not fully capture the functions of English in Viet Nam. We therefore propose expanding the EIL conceptualization to encompass the intra-national use of English for EMI. This suggests implications for English language teaching to better prepare Vietnamese learners with the English they need for their studies and future professions.